Dinamika Penerapan Kurikulum Merdeka di Sekolah Dasar: Tinjauan Literatur Sistematis - Bayu Kurniawan; Fitri Puji Rahmawati; Anik Ghufron (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The Merdeka Curriculum implemented by the government since 2022 aims to provide opportunities for schools to carry out learning activities according to their potential and excellence. This research offers a new contribution with a systematic approach in reviewing various studies related to the implementation of the Merdeka Curriculum in elementary schools and allows the identification of best practices and effective strategies, which can be applied in various contexts. This research is a systematic literature review, which aims to comprehensively and critically review existing research related to the implementation of the Merdeka Curriculum in elementary schools in Indonesia. The article used is the latest publication period 2022-2024. General problems that often arise in implementing the Independent Curriculum: (1) Teachers do not fully understand the Independent Curriculum; (2) Lack of teacher competence in teaching, and; (3) Lack of support for facilities and infrastructure for the teacher learning process. The solutions offered can be summarized as follows: (1) Teachers can take part in training or workshops to understand the application of the Independent Curriculum and develop learning methods, models and strategies; (2) Collaboration between teachers, either personally or in Teacher Working Group forums or through professional teacher organizations; (3) Coordination of all stakeholders in socializing the implementation and evaluation of the Independent Curriculum; (4) Involvement of teachers in curriculum development, and; (5) The active role of stakeholders and parents in providing facilities and infrastructure.